Characterizing a syntactic pattern of formgiving in design thinking process / Rusmadiah Anwar - Anwar, Rusmadiah (2016)
Design in a creative way involves a high degree of enigmatic and mystery especially at the early stage of a project. On the whole, conventional industrial design investigation faced with numerous of dilemma especially on the design methodology. The unclear design approach practiced among the creatlve designers comes to the techmcal hitches to introduce a new product design. The challenge of current trends In design research and point out some of their acxivities, such as the gap between aesthetic and technical need, and the chasm between ambiguous and quantified m design practice, In line with the awareness of high-quality aesthetic appeal in industrial product development, therefore, exist a need to revamp this uncertainty design activity (form stmcturing) for more accurate and being understood during the decision making in product synthesis. This used together with the enhanced understanding and ability to handle Visual product form, necessitate stmcturing throughout the creatlve process, In order to deal with these problems, it is recommended to develop a research guideline on the observafiun setup procedure. These promlses to improve the ecological validity over the empirical design research methodology include the possible sampling required. The main goal of the analyzes is to formulate a methodology for analyzing qualitanvc data in an objective way. The design practice was analyzed through empirical design studies to uncovcr the design thinking approaches and their standpoint on design solutions throughout formgiving process. The results also discussed the solution to both initial problems of de51gn activitles. Through the empirical framework of in-Vitm deslgn protocol, a descriptive model of the nature and workings of the ablution design as a subject is identified. The framework consists of two main control experiment phases; design protocol analyIs, concerning the behaviour of designer during design episode; and meta-analysis, related to the characterizing stage of form syntactic related to the actiVIty of organization and structure of visual product form. The result ‘hrough circumstantial evidence from both approaches reveaied that [here is a consistency character that emerge the pruduct perceptual experience during formgiving processes. The insight seeking and form element ordering during design episode has exposed the divergentconvergent ofAblution Function Mean Analysis thinking among designer generates a significant visual surface features of the form structure. Based on the mam-analysis results, the formgiving presentation confirmed ‘he intuition conceptually presented a strategic plan of aesthetic influence through the conceptual and embodiment design, While the representation of syntactic pattem through Dual-Trace Explicit Implicit has aesthetically determined the cxistmg of intuitive gestalt interplay during the creation of form structure. As the main contribution of this work is: (l) the creation of core empirical method relates to rexearchfar design as 'possible versus feasiblc’ through explicit-implicit strategy; (2) conducted research relates to research into design as ‘specific Versus hulistic’ through the determination of talent, intuition and form syntactic; and (3) presented research relates research through design as ‘global versus detailed' through the establishment of Variables between design perceptual and behaviour.